Tindak Tutur Ilokusi dalam Pidato Wamenlu RI Anis Matta pada KTT Luar Biasa OKI 2024 : Illocutionary Acts in the Speech by Indonesian Deputy Minister of Foreign Affairs Anis Matta at the 2024 Extraordinary OIC Summit - Siti Ainun Nuriyah; Fahmy Lukman; Muhammad Zulfi Abdul Malik (Language Development Center, 2026)
Background: This study examines illocutionary speech acts in Anis Matta's Arabic speech at the 2024 Extraordinary OIC Summit. The speech was delivered as Indonesia's response to the humanitarian crisis in Palestine and sought to encourage a collective response from Arab and Islamic countries. It drew widespread attention because it was delivered in Arabic by a non-Arab diplomat, demonstrating how language was strategically employed as an instrument for shaping perception and building legitimacy in international forums. Purpose: This study aims to analyze the forms and functions of illocutionary speech acts in Anis Matta's speech at the 2024 Extraordinary OIC Summit using a pragmatic approach. Method: This study employs a descriptive qualitative approach with data sourced from Anis Matta's Arabic speech accessed through the YouTube channel of the Indonesian Ministry of Foreign Affairs. Data were collected through non-participatory observation and note-taking techniques. The data were analyzed using Searle’s (1979) speech act theory and Leech’s (1983) illocutionary function framework through the extralingual identity method to analyze utterances based on their speech context. Results and Discussion: The results show that four forms of illocutionary speech acts were identified in the speech with a total of 24 utterances, namely assertive 12 utterances (50%), expressive 7 utterances (29.17%), directive 4 utterances (16.67%), and commissive 1 utterance (4.17%), while the declarative form was not found. The dominance of assertive acts reflects the speaker's role as an official state representative delivering statements and proposals in a diplomatic forum. The illocutionary functions identified include competitive 12 utterances (50%), convivial 7 utterances (29.17%), and collaborative 5 utterances (20.83%), while the conflictive function was not found. The dominance of competitive functions indicates that the speech conveys demands and proposals addressed to member states while maintaining diplomatic politeness. These findings suggest that assertive and directive utterances in the form of proposals and demands tended to function competitively, while expressive utterances tended to function convivially and assertive utterances in the form of statements tended to function collaboratively. Conclusions and Implications: This study reveals that the use of Arabic in diplomatic speech reflects the speaker's communication strategy in international forums. It contributes to the field of Arabic pragmatics, particularly in the analysis of illocutionary speech acts in diplomatic discourse. Future research may examine a wider range of Arabic diplomatic speeches, conduct comparative analyses across speeches, and explore perlocutionary aspects to broaden understanding of pragmatic strategies in diplomatic discourse.